The Effect of Height and Water Discharge on the Output of Electrical Energy Generated at the Sawitto Micro-Hydro Power Plant (PLTM) in Pinrang Regency - Syamril, Syamril; Yusuf Mappeasse, Muhammad; Hermansyah, Hermansyah (Energy Insights, 2026)
Objective: This study aims to analyze the relationship between water discharge and water level and their influence on electrical output performance in a Micro Hydro Power Plant (PLTM) using empirical operational data from the Sawitto PLTM in Pinrang Regency, Indonesia. Methods: A quantitative ex-post facto research design was employed using monthly operational data on water discharge, water level, and electrical output collected from three generating units. The data were analyzed using descriptive statistics and multiple linear regression modeling implemented in Microsoft Excel and MATLAB. Statistical significance was evaluated using t-tests for partial effects and F-tests for simultaneous effects to assess the reliability of the predictive model. Results: The regression analysis indicates that water discharge and water level collectively explain a substantial proportion of the variation in electrical output, as reflected by high coefficients of determination across generating units. However, individual statistical tests revealed that neither variable was statistically significant at the 5% level, suggesting that additional technical and operational factors, such as turbine efficiency, mechanical condition, hydraulic losses, and seasonal water availability, influence system performance. The findings also reveal discrepancies between theoretical and actual power output, indicating the presence of efficiency losses and operational constraints under field conditions. Novelty: This study provides empirical evidence based on real operational data from a rural micro-hydro power plant and offers a practical engineering perspective by highlighting the interaction between hydrological variability and technical system performance, offering insights for improving predictive modeling and operational management of small-scale renewable energy systems.